Schirmer tear test I and rebound tonometry findings in healthy calves. (27th March 2014) - Tofflemire, Kyle L.; Whitley, Elizabeth M.; Gould, Stacie A.; Dewell, Renee D.; Allbaugh, Rachel A.; Ben‐Shlomo, Gil; O'Connor, Annette M.; David Whitley, R.
Abstract Objective To describe Schirmer tear test I and rebound tonometry findings in healthy bovine calves. Animals studied Thirty‐three clinically normal dairy breed calves of mean (SD) 11 (1.1) weeks (range, 9.3–13.3 weeks) of age were evaluated. Procedures A Schirmer tear test I was performed on each eye followed by tonometry, using a TonoVet® without topical anesthesia. We report means (SD) and statistical analysis of data for each assay. Results For both Schirmer tear test (STT) I and tonometry, significant differences were not found between fellow eyes (P = 0.1536 and P = 0.83, respectively). The mean (SD) STT I value of all eyes was 20.4 (5.0) mm/min (range, 9–34 mm/min) while the mean (SD) intraocular pressure (IOP) value of all eyes was 15.2 (5.2) mmHg (range, 7–25 mmHg). Conclusions This study reports normal data for the STT I and rebound tonometry in calves. This data may be useful in complete ophthalmic examinations of cattle, guiding diagnosis of glaucoma, uveitis, and keratoconjunctivitis sicca. However, results of these diagnostic modalities must be interpreted in light of clinical signs, given the wide range of normal values obtained in this study.